PENGEMBANGAN VIDEO PEMBELAJARAN MATERI KLASIFIKASI HEWAN SEBAGAI SUPLEMEN BAHAN AJAR BIOLOGI SMP - Yusriya, Arina; Santosa, Kukuh; Priyono, Bambang (Journal of Biology Education, 2014)
Â Video can be use as biology learning material supplement for animal classification that have an unprecise concept. This study aims to develop and assess the feasibility of animal classification video as biology learning material supplement for SMP. The study is Research and Development (R&D), the steps are potency and problem identification, data collection, product design (video), video evaluation and revision, limited trial and revision, wide-scale trial and revision, final production. In limited trial using VII D class which amounts to 30 students and wide-scale trial using VII A and VII E class which amounts 60 students. The datas of this study are determined from the evaluation of video by medium and material validator, teacher and students responses, and student learning outcomes. Video evaluation by medium and material validator gets average score 93,75% (very good). Students give positive responses, it shows by 86,7% of students give very good responses and 5% of students give good responses. Teacher also give positive response about video using in learning. Studentâs completeness learning outcomes with the score â¥82 in VII A class reached 86,67% and 90% in VII E class. The conclusion of this study are animal classification video is developed with some steps and it suitable to be used as biology learning material supplement for SMP.Video pembelajaran dapat digunakan sebagai suplemen bahan ajar biologi materi klasifikasi hewan yang bersifat abstrak. Penelitian ini bertujuan untuk mengetahui proses pengembangan dan kelayakan video pembelajaran materi klasifikasi hewan sebagai suplemen bahan ajar biologi SMP. Penelitian ini merupakan penelitian Research and Development (R&D) yang melalui tahapan identifikasi potensi dan masalah, pengumpulan data, desain produk (video), validasi video dan revisi, uji coba awal dan revisi, uji coba pemakaian dan revisi, produksi final. Uji coba awal dilakukan pada 30 orang siswa kelas VII D dan uji coba pemakaian dilakukan pada 30 siswa kelas VII A dan 30 siswa kelas VII E. Data yang diperoleh berupa penilaian ahli materi dan ahli media, tanggapan guru dan siswa, serta hasil belajar siswa. Penilaian video pembelajaran oleh ahli media dan ahli materi memperoleh skor rata-rata 93,75% (sangat baik). Siswa memberikan tanggapan positif, hal ini ditunjukkan dengan 86,7% siswa memberikan tanggapan sangat baik dan 5% memberikan tanggapan baik. Guru juga memberikan tanggapan positif terhadap penggunaan video dalam pembelajaran.Â  Ketuntasan hasil belajar pada kelas VII A mencapai 86,67% dan pada kelas VII E mencapai 90%. Simpulan dari penelitian ini adalah video pembelajaran materi klasifikasi hewan dikembangkan melalui beberapa tahapan dan layak digunakan sebagai suplemen bahan ajar biologi SMP.